Organizational Citizenship Behavior as a Relationship to Job Satisfaction among Handball Teachers in Colleges and Departments of Physical Education and Sports Science (Damu Journal of Sport Sciences, 2025)
scientific foundations, relying on modern administrative methods that ensure the provision of public services in the shortest possible time and at the lowest possible cost. If we want sports to flourish and advance, it must adopt the path of science, and management is one of the fundamental scientific pillars upon which all countries of the world rely.The objectives of the research were to develop measures of organizational citizenship behavior and satisfaction, to identify organizational citizenship behavior and job satisfaction among handball teachers in colleges and departments of physical education at Iraqi universities, and to determine the correlation between the variables.The researchers used the descriptive approach using a survey method, correlational relationships, and predictive studies. The research community included all handball professors in the colleges and departments of physical education and sports sciences in Iraqi universities for the academic year (2024-2025), totaling (140) professors. One of the most important conclusions of the researchers is that handball professors in the colleges and departments of physical education and sports sciences in Iraqi universities have similar scores in organizational citizenship behavior and job satisfaction, as well as the existence of a positive correlation between organizational citizenship behavior and job satisfaction among professors.